(3 - 4x²)(4x² + 3) = ?????
Răspunsuri la întrebare
Răspuns de
1
= - ( 4x patrat - 3 ) ( 4x patrat + 3 )
= - [ ( 4x patrat ) patrat - 9 ]
= - ( 16x la puterea 4 ) - 9
= -16x la puterea 4 + 9
= 9- 16 x la puterea 4
= - [ ( 4x patrat ) patrat - 9 ]
= - ( 16x la puterea 4 ) - 9
= -16x la puterea 4 + 9
= 9- 16 x la puterea 4
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Chimie,
10 ani în urmă
Istorie,
10 ani în urmă
Geografie,
10 ani în urmă